A Study on Preventive System against Recidivism of Retaliatory Crime using IOT-based Smart Watch - OH, Sei-Youen; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The study recognizes a seriousness of recidivism of retaliatory crimes and, in order to resolve the issue, proposes a preventive system against recidivism of retaliatory crimes by utilizing a IOT-based smart watch, which enables minimization of damage from retaliatory crimes and crime prevention.Methods/Statistical analysis: In a discussion of retaliatory crimes and a smart watch, formal statistical figures from the National Police and the Supreme Prosecutorsâ€™ Office were observed and a system module has been established, enabling minimization of damage from retaliatory crimes by additionally editing functions based on a preexisting module, a smart watch operation method for personal protection currently in-use by the National Police, so that a possibility of a retaliatory crime occurrence can be detected.Findings: The society recently has recognized the seriousness of retaliatory crimes in relation to Stalking, dating violence and domestic violence, and has actively strived for precautionary and responsive measures against retaliatory crimes with judicial authorities. Therefore the preventive system against recidivism of retaliatory crimes by using a IOT-based smart watch let received data from victims wearing a smart watch with sensors be transferred to a monitoring module. Particularly, not only having sensors, the smart watch has additional functions to record and film the scene automatically and to minimize an error range of location tracking and appoint a specific building position. Then, a chance of possible recidivism of retaliatory crime occurrences related to the received data from a smart watch is determined within the monitoring module. If any possible retaliatory crime occurrence is expected, a crime responding module is activated, otherwise, the received data is deleted. Furthermore, the collected data from the crime responding module and from those who are wearing a smart watch are stored in an integrated DB and are used to improve countermeasures against future retaliatory crimes.Improvements/Applications: The system can identify the chance of recidivism of retaliatory crimes in advance through a monitoring module and a smart watch equipped with various sensors. Furthermore, the crime responding module is performed in 4-phases, which ensures sufficient time for the police to be mobilized, delays criminal acts, minimize damage from the crimes and enables rapid countermeasures.Â Â